Depressive Symptoms and Self-Esteem in White and Black Older Adults in the United States - Shervin Assari; Maryam Moghani Lankarani (Brain Sciences, 2018)
Background. Poor self-esteem is a core element of depression. According to recent research, some racial groups may vary in the magnitude of the link between depression and poor self-esteem. Using a national sample, we compared Black and White older Americans for the effect of baseline depressive symptoms on decline in self-esteem over time. Methods. This longitudinal study used data from the Religion, Aging, and Health Survey, 2001–2004. The study followed 1493 older adults (734 Black and 759 White) 65 years or older for three years. Baseline depressive symptoms (CES-D), measured in 2001, was the independent variable. Self-esteem, measured at the end of the follow up, was the dependent variable. Covariates included baseline demographic characteristics (age and gender), socioeconomic factors (education, income, and marital status), health (self-rated health), and baseline self-esteem. Race/ethnicity was the moderator. Linear multi-variable regression models were used for data analyses. Results. In the pooled sample, higher depressive symptoms at baseline were predictive of a larger decline in self-esteem over time, net of covariates. We found a significant interaction between race/ethnicity and baseline depressive symptoms on self-esteem decline, suggesting a weaker effect for Blacks compared to Whites. In race/ethnicity-specific models, high depressive symptoms at baseline was predictive of a decline in self-esteem for Whites but not Blacks. Conclusion. Depressive symptoms may be a more salient contributor to self-esteem decline for White than Black older adults. This finding has implications for psychotherapy and cognitive behavioral therapy of depression of racially diverse populations.